Systemic and local effects of radiotherapy: an experimental study on implants placed in rats - da Cruz Vegian, Mariana Raquel [UNESP]; Costa, Bruno César Almeida [UNESP]; de Fátima Santana-Melo, Gabriela [UNESP]; Godoi, Fernanda Herrera Costa [UNESP]; Kaminagakura, Estela [UNESP]; Tango, Rubens Nisie [UNESP]; do Prado, Renata Falchete [UNESP]; de Oliveira, Luciane Dias [UNESP]; Federico, Claudio Antonio; de Oliveira Marco Avelino, Sarah [UNESP]; Neves, Rafael Marques [UNESP]; de Vasconcellos, Luana Marotta Reis [UNESP] (Springer Nature, 2019)
Objectives: Evaluate the modulating effect of ionizing radiation, blood cytokine levels, and bone remodeling of the interface around the implant to understand the radiation mechanisms which can impair the implants receptor site. Material and methods: Sixty rats were submitted to grade V titanium implants in the femurs and were divided into the following groups: no-irradiation (N-Ir): control group with implant only; early-irradiation (E-Ir): implant + irradiation after 24 h; late-irradiation (L-Ir): implant + irradiation after 4 weeks; and previous-irradiation (P-Ir): irradiation + implant after 4 weeks. The animals in the E-Ir, L-Ir, and P-Ir groups were irradiated in two fractional stages of 15 Gy. At 3 days, 2 weeks, and 7 weeks after the final procedure, five animals were randomly euthanized per group. Serum levels of TNF-ɑ, IL-1β, TGF-β, IL-6, M-CSF, and IL-10 were measured from blood collected prior to euthanasia using the ELISA test. The pieces containing the implants were subjected to immunohistochemical labeling using the tartrate acid resistant to phosphatase, osteocalcin, and caspase-3 markers and mCT. The ANOVA test was used for statistical analysis, and the Tukey multiple comparison test (p < 0.05) was applied. Results: The results indicated that ionizing radiation modifies the production of pro- and anti-inflammatory serum cytokines, the expression of proteins involved in bone remodeling and cellular apoptosis, as well as changes in bone formation. Conclusions: The results suggests that a longer period between radiotherapy and implant placement surgery when irradiation occurs prior to implant installation would allow the recovery and renewal of bone cells and avoid future failures in osseointegration. Clinical relevance: The search for modifications caused by ionizing irradiation in bone tissue can indicate the ideal period for implant placement without affecting the osseointegration process.
Keywords: Bone remodeling; Cytokines; Immunohistochemistry; Radiotherapy; Titanium implants